THE TRANSPOSITION OF THE EUROPEAN SOCIAL PARTNERS’ AGREEMENTS INTO NATIONAL LAW - Bagdonaitė, Aušra (Teisė, 2017)
This article focuses on the transposition of the European social partners’ agreements into national law. Firstly, the genesis of these agreements in the context of the European Union social-economic policy and the essence of their content are presented. The research aims to identify the theoretical preconditions of the appropriate transposition of autonomous framework agreements, concluded by the European social partners, into national law of the European Union Member States as well as to evaluate their practical implementation regarding the experience of certain Member States.